Respiratory Depression on the Wards: Why Better Monitoring may be the Answer? - Ashish K. Khanna (Research and Practice in Anesthesiology, 2017)
Although, deaths during anesthesia are rare, deaths in the post-operative period are not. The third leading cause of death in the United States is mortality after surgery, during the ‘recovery and rehabilitation’ period.2 The most common cause of 30-day post-operative mortality unsurprisingly, is cardiorespiratory complications.